Making a Difference for Kansans, FY2014 - Floros, John D. (My University, 2014)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2014, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN28_2014_01
Keywords: UNN28; Administrative and Research Reports; legislature